Characterization of gastrointestinal pathologies in the dystonia musculorum mouse model for hereditary sensory and autonomic neuropathy type VI. Issue 4 (9th December 2019) - Lynch‐Godrei, Anisha; De Repentigny, Yves; Yaworski, Rebecca A.; Gagnon, Sabrina; Butcher, James; Manoogian, Juliana; Stintzi, Alain; Kothary, Rashmi
Abstract: Background: Dystonia musculorum ( Dst dt ) is a murine disease caused by recessive mutations in the dystonin ( Dst ) gene. Loss of dorsal root ganglion (DRG) sensory neurons, ataxia, and dystonic postures before death by postnatal day 18 (P18) is a hallmark feature. Recently we observed gas accumulation and discoloration in the small intestine and cecum in Dst dt mice by P15. The human disease resulting from dystonin loss‐of‐function, known as hereditary sensory and autonomic neuropathy type VI (HSAN‐VI), has also been associated with gastrointestinal (GI) symptoms including chronic diarrhea and abdominal pain. As neuronal dystonin isoforms are expressed in the GI tract, we hypothesized that dystonin loss‐of‐function in Dst dt‐27J enteric nervous system (ENS) neurons resulted in neurodegeneration associated with the GI abnormalities. Methods: We characterized the nature of the GI abnormalities observed in Dst dt mice through histological analysis of the gut, assessing the ENS for signs of neurodegeneration, evaluation of GI motility and absorption, and by profiling the microbiome. Key results: Though gut histology, ENS viability, and GI absorption were normal, slowed GI motility, thinning of the colon mucous layer, and reduced microbial richness/evenness were apparent in Dst dt‐27J mice by P15. Parasympathetic GI input showed signs of neurodegeneration, while sympathetic did not. Conclusions & Inferences: Dst dt‐27J GI defects are not linked to ENS neurodegeneration, but are likely a result of an imbalance in autonomic control over the gut. Further characterization of HSAN‐VI patient GI symptoms is necessary to determine potential treatments targeting symptom relief. Abstract : Dystonia musculorum mice ( Dst loss‐of‐function; Dst dt‐27J ) show gastrointestinal abnormalities such as gas accumulation, intestinal distension, discoloration, and diarrhea. While these observations could not be explained by neurodegeneration of the enteric nervous system, it's likely that an autonomic imbalance (favoring sympathetic input) is responsible for these changes.